A clinical study of etiology and management of acute intestinal obstruction - C.R, Shivakumar; Shoeb, Mohammad Fazelul Rahman; Reddy, Anil P.; Patil, Sharangouda (International Surgery Journal, 2018)
Background: Acute intestinal obstruction is one of common abdominal emergency and is associated with significant morbidity and mortality. Early diagnosis of obstruction, skilful operative management, proper technique during surgery and intensive postoperative treatment carries better results. The aim of this study was to identify the etiology, clinical presentation, management and outcomes of patients with acute intestinal obstruction presenting in GIMS, Gulbarga. Methods: This is a prospective study carried out in the department of general surgery A unit at Gulbarga Institute of Medical Sciences, Gulbarga, from May 2014 to January 2018. 50 patients with acute intestinal obstruction coming to the OPD and emergency department were included in study and data was analysed. Results: A total of 50 patients, presented with acute intestinal obstruction during the period of the study. Mean patient age was 46.5 years with peak incidence in 50-59 years. Small intestinal obstruction was seen more commonly than large intestinal obstruction. Most common etiology of intestinal obstruction was due to adhesion and bands (40%). Conclusions: Present study concluded that Intestinal obstruction is seen more commonly in middle age group. Males were affected twice as common as females. Abdominal pain was the most common symptom, while tenderness was the most common sign. Post-operative adhesion caused most cases of small bowel obstruction while large bowel obstruction was caused most commonly by malignancy. Earlier the presentation better will be the outcome.